Rancang Bangun Alat Pemilah Sampah Otomatis Berbasis Arduino Mega 2560 - Ernes Cahyo Nugroho; Anton Respati Pamungkas; Ika Parlina Purbaningtyas (Go Infotech: Jurnal Ilmiah STMIK AUB, 2018)
Dumpster management system on Village/Warukkalong Village, RT/RW: 05/01, Kecamatan Kwadungan, Ngawi, East Java still conventional, i.e. the place one container of trash and garbage not disposed of according the trash, which affects trash piled up on one container of trash that impact to the declining environmental quality. Automatic trash can is one of the alternatives that can be used to sort out the type of garbage so that waste management more effectively in order to increase comfort and maximum possible waste reduction. Parser tools architecture garbage garbage sorting type aiming for, so that waste can be separated based on the type of waste, whether inorganic or organic waste garbage can be processed. The garbage will be disaggregated automatically by using a Sensor. The sensor used in auto IE trash proximity capacitive to detect an-organic, as well as inductive proximity to detect the types of bins, and Ultrasonic sensors to detect the height of the garbage and LCD to display the condition and type of garbage. The results of testing on the bin automatically is the maximum size that can be entered approximately 5 cm x 10 cm with a time of 10-17 seconds from the first go in the garbage into the trash until the end.